Electronic Structure and X-Ray Magnetic Circular Dichroism in (Zn, T)O (T = V, Fe, Co) Diluted Magnetic Semiconductors - Bekenov, L.V.; Mazur, D.V.; Antonov, V.N.; Germash, L.P.; Erns, t A. (Металлофизика и новейшие технологии, 2013)
The electronic structure of the (Zn, T)O (T = V, Fe, Co) diluted magnetic semiconductors is investigated theoretically from first principles, using the fully relativistic Dirac linear muffin-tin orbital band structure method. The X-ray absorption spectra, X-ray magnetic circular dichroism spectra at the Co, Fe, and V L2,3 edges are investigated theoretically. The origin of the dichroism spectra in such compounds is examined. Using the magnetic force theorem, as it is implemented within the multiple scattering theory, the exchange interaction parameters for the transition metal atoms are calculated. За допомогою зонної повністю релятивістської лінійної методи МТ-орбіталей теоретично досліджено з перших принципів електронні структури розбавлених магнетних напівпровідників (Zn, T)O (T = V, Fe, Co). Теоретично досліджено спектри поглинання Рентґенового випромінення і спектри Рентґенового магнетного циркулярного дихроїзму на L2,3-краях поглинання атомів Co, Fe та V. Вивчено природу спектрів дихроїзму в цих сполуках. За допомогою теореми про магнетні сили на основі теорії багатократного розсіяння було обчислено параметри обмінної взаємодії між атомами перехідних металів. Электронная структура разбавленных магнитных полупроводников (Zn, T)O (T = V, Fe, Co) исследована теоретически, исходя из первых принципов, полностью релятивистским линейным методом МТ-орбиталей. Теоретически исследованы рентгеновские спектры поглощения и спектры рентгеновского циркулярного дихроизма на L2,3-краях поглощения атомов Co, Fe и V. Изучена природа спектров дихроизма. С помощью теоремы о магнитных силах на основе теории многократного рассеяния вычислены параметры обменного взаимодействия между атомами переходных металлов.